Comparisons between impedance-based and time-based switching bipolar radiofrequency ablation for the treatment of liver cancer. (July 2021) - Yap, Shelley; Ooi, Ean H.; Foo, Ji J.; Ooi, Ean T.
Abstract: Switching bipolar radiofrequency ablation (bRFA) is a cancer treatment technique that activates multiple pairs of electrodes alternately based on a predefined criterion. Various criteria can be used to trigger the switch, such as time (ablation duration) and tissue impedance. In a recent study on time-based switching bRFA, it was determined that a shorter switch interval could produce better treatment outcome than when a longer switch interval was used, which reduces tissue charring and roll-off induced cooling. In this study, it was hypothesized that a more efficacious bRFA treatment can be attained by employing impedance-based switching. This is because ablation per pair can be maximized since there will be no interruption to RF energy delivery until roll-off occurs. This was investigated using a two-compartment 3D computational model. Results showed that impedance-based switching bRFA outperformed time-based switching when the switch interval of the latter is 100 s or higher. When compared to the time-based switching with switch interval of 50 s, the impedance-based model is inferior. It remains to be investigated whether the impedance-based protocol is better than the time-based protocol for a switch interval of 50 s due to the inverse relationship between ablation and treatment efficacies. It was suggested that the choice of impedance-based or time-based switching could ultimately be patient-dependent. Graphical abstract: Image 1 Highlights: Impedance-based switching was better than time-based for switch intervals ≥100 s. Impedance-based bRFA deliver lower RF energy to the tissue compared to model s 50 . Coagulation volume obtained using impedance-based bRFA was smaller than model s 50 . Impedance-based bRFA produced higher ablation efficacy than model s 50 . Impedance-based bRFA produced lower treatment efficacy than model s 50 .